Stereocontrolled route to the synthesis of (+/-)-3-amino-2,2-dimethyl-1,3-diphenylpropan-1-ol - Patil, M. N.; Bhowmick, Kartick C.; Joshi, Navalkishore N. (Tetrahedron Letters, 2010)
Both the diastereomers of (+/-)-3-amino-2,2-dimethyl-1,3-diphenylpropan-1-ol were synthesized starting from a common intermediate, namely,B-hydroxy, oxime 6. Diastereoselective reduction with NaBH(4)/TiCl(4) and H(2)-Pd/C provided syn- and anti-isomers, respectively. Good overall yield and selectivity were realized using a simple protocol. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: 1; 3-Aminoalcohol; Aldol-Tishchenko reaction; beta-Hydroxy oxime; Diastereoslective reduction